(untitled) (Al-Qamar, 2020)
Pakistan is perhaps a country where one of the major reasons for severe riots is ‘Takfīr’. Depicting its nature and causes, the present article identifies the worse effects of Takfīrī attitude in Pakistani society and gives applicable methods and strategies to curb this approach. It has valuable suggestions on how we can get rid of this malice from our homeland. It concludes that religious extremism leads towards destruction and to save Pakistan from catastrophe, it is necessary to take steps to control extremism and Takfīrī trend from this society.